Factors Influencing Employee Creativity in Higher Education: A Bibliometric Analysis, Systematic Literature Review, and Future Research Directions - Qiuhong Wu; Syaharizatul Noorizwan Muktar; Hakimah Muhammad Zin; Fangyin Tian (Environment and Social Psychology, 2026)
Despite extensive research on employee creativity and its impact on employee and organizational outcomes in management, there is a scarcity of studies examining this topic in higher education. The limited research focusing on education suggests a prevalent lack of employee creativity among educational institutions. To address this research gap, we conducted a systematic analysis of empirical studies on the factors influencing employee creativity in higher education published up to November 2024, employing a combination of bibliometric and content analysis methods. Our findings provide a comprehensive overview of the field, identifying influential works and analyzing scholarly communication among them. Furthermore, the study clarifies the research network’s central themes and structural characteristics on employee creativity in higher education. We conclude by discussing future research directions, aiming to foster a deeper understanding and advancement of employee creativity within higher educational settings.